Pernikahan Dini dalam Perspektif Psikologi Komunikasi - Abdi Fauji Hadiono (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2018)
This research is directed to two main things namely, (1) Factors Cause Early Marriage. (2) The Impact of Early Marriage. Methods of data collection: Interview, Participant Observation and Documentation with a qualitative approach. Data analysis using interactive model, which consists of three components, namely: data reduction (data reduction), data presentation (Data Display) withdrawal and testing (Drawing and Verifying Conclusion). The conclusion of research in Barurejo Village found that there are several factors of early marriage which include education factor, economic factor, and free association factor. Researchers also found some impacts that occur due to early marriage that includes positive impacts that comprise the economic and religious aspects. While the negative impact is seen in terms of mental, educational and health aspects.